Sustainable Development in Vietnam: The Interconnectedness of Climate Change, Socio-Economic Development, Land Use, and Food Security - Erica Davis (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2016)
In response to climate change, many nations are facing a crisis in regards to managing land use, mitigating environmental degradation, and otherwise pursuing sustainable development. Vietnam faces many unique circumstances, both historical and present, that make it an interesting case study in such topics. As the discernable impacts of climate change increase, it is necessary for Vietnam to pursue policies that are holistic and effective, especially considering the extreme vulnerability of the nation’s inhabitants. The most important factors to consider are climate change, socio-economic development, land use, and food security—especially how these concepts intertwine to create the reality of Vietnam’s political, ecological, and social landscape.